Partial-Thickness Tear of Supraspinatus and Infraspinatus Tendon Revisited: Based on MR Findings - Sinhye Song (The Korean Society of Radiology, 2021)
The interpretation of MRI of partial-thickness rotator cuff tears can be challenging. This review describes the anatomic considerations for diagnosing partial-thickness tears, especially supraspinatus and infraspinatus tendon and summarizes the classification of partial-thickness rotator cuff tears, as well as provides an overview on partial-thickness tears with delamination.